Pemaknaan Konten Youtube Fadil Jaidi Tentang Adab Kepada Orang Tua (Studi Resepsi pada Subscriber Millennial) - Wahdiyati, Dini; Ovita Violina, Kiki (Jurnal Indonesia Sosial Sains, 2023)
Youtube is indeed a substitution for a means of watching the content that can surpass television. The advantage of Youtube as a viewing medium is that it presents thematic shows that can be very closely related to the audience according to their respective interests. Thus the media of this era is very intimate with its users as well as its influence which will be more multiplying. This research examines the meaning of millennial viewers subscriber to Fadil Jaidi's Youtube channel who presents content in the form of witty activities and interactions by involving his father as a content attraction. Millennial subscribers as objects of warning were chosen because they are native viewers of Youtube media. The focus of this study looked at the audience meaning of the content of the episode "The Story Becomes a Slang Child" directed at how the meaning of the content about adab towards parents in the content was studied through Stuart Hall's reception theory and reception analysis methods. This research found that Millennial Dominant hegemonic audiences accept this content as an alternative to entertainment, Negotiated position viewers see more selectively on both sides, namely the positive and negative of the content while Oposition viewers interpret by rejecting behavior in the content because it is considered less civilized to parents. The dominant hegemonic acceptance factor, Negotiated position and Oposition are influenced by cultural identity factors, environment, experiences and parenting backgrounds of each receptor.